ANALISIS KETERLAMABATAN DENGAN METODE STOKASTIK DAN MITIGASI RISIKO (Studi Kasus : Proyek Instalasi Pengolahan Air Limbah B1 Kota Pekanbaru) - zulfiandri - zulfiandri; Ari Sandhyavitri; Muhamad Yusa (Racic : Rab Construction Research, 2024)
The issue of environmental pollution has become a strategic issue because of its chain effects on all aspects of life. The construction of the City of Pekanbaru wastewater treatment facility is aimed at the treatment of domestic wastewater due to the density of the population and economic activity so that the quality of the environment is awakened. In this study, the risk of delay in the construction of a sewage treatment facility B1 in Pekanbaru was identified using the Relative Importance Index. (RII). The actual work duration is delayed against the duration of the original plan. Risk analysis uses a stochastic approach to the duration of work. In this analysis, the probability distribution function triangle distribution with 3-point estimate is used. This risk simulation uses @risk software with a maximum of 100,000 iterations. Work in the critical trajectory plays a crucial role in setting the project completion timetable. Initially, the estimated time of execution of the work was 1,075 days. After the analysis (Risk Pert Before Mitigation) the execution time with a 95% confidence rate reached 1,370 days, suggesting a potential delay of 295 days.